Answer :

A quadratic equation when sum and product of its zeros is given by:

, where k is a constant

Sum of the roots = = = =

Product of the roots = = =

Sum of the zeros of new eqn = = =

⇒ 2×-2× = 2-) [Using (a + b)^{2} = a^{2} + b^{2} + 2ab]

Product of the zeros of new eqn = =

⇒

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

In the given figuRS Aggarwal - Mathematics

Find all the zeroMathematics - Board Papers